A newly developed genetic sex marker and its application to understanding chemically induced feminisation in roach (Rutilus rutilus). (15th June 2020) - Lange, Anke; Paris, Josephine R.; Gharbi, Karim; Cézard, Timothée; Miyagawa, Shinichi; Iguchi, Taisen; Studholme, David J.; Tyler, Charles R.
Abstract: Oestrogenic wastewater treatment works (WwTW) effluents discharged into UK rivers have been shown to affect sexual development, including inducing intersex, in wild roach ( Rutilus rutilus ). This can result in a reduced breeding capability with potential population level impacts. In the absence of a sex probe for roach it has not been possible to confirm whether intersex fish in the wild arise from genetic males or females, or whether sex reversal occurs in the wild, as this condition can be induced experimentally in controlled exposures to WwTW effluents and a steroidal oestrogen. Using restriction site‐associated DNA sequencing (RAD‐seq), we identified a candidate for a genetic sex marker and validated this marker as a sex probe through PCR analyses of samples from wild roach populations from nonpolluted rivers. We also applied the sex marker to samples from roach exposed experimentally to oestrogen and oestrogenic effluents to confirm suspected phenotypic sex reversal from males to females in some treatments, and also that sex‐reversed males are able to breed as females. We then show, unequivocally, that intersex in wild roach populations results from feminisation of males, but find no strong evidence for complete sex reversal in wild roach at river sites contaminated with oestrogens. The discovered marker has utility for studies in roach on chemical effects, wild stock assessments, and reducing the number of fish used where only one sex is required for experimentation. Furthermore, we show that the marker can be applied nondestructively using a fin clip or skin swab, with animal welfare benefits.